Voltammetric behavior of ketoconazole and its determination in cosmetic preparation using a β-cyclodextrin modified glassy carbon electrode - M.A. El Ries; M.F. Abdel Ghany; L.A. Hussin; Fawzy M. El-Anwar; A.M. Mohamed (Faculty of Pharmacy, Cairo University, 2013)
A voltammetric determination of ketoconazole (KCZ) at a beta-cyclo-dextrin modified glassy carbon (CDMGC) is described. A large increase in the peak currents was observed in cyclic voltammetry (CV) and differential pulse voltammetry (DPV) of KCZ. This increase in the big current were attributed to the complex formation of the KCZ with β-cyclodextrin. CV studies indicate that the process is irreversible and adsorption-controlled. The effect of pH, scan rate, cyclodextrin concentration and stability of electrodes on the current responses of KCZ was studied. The linearity was obeyed over the concentration range (1-8 × 10−5 mole/l) with a common correlation coefficient and limit of detection of 0.9996 and 10.54 × 10−8, respectively, in pH 9 Britton-Robinson (BR) buffer. The modified electrode exhibited good sensitivity, and stability. The voltammetric method was successfully applied for the determination of KCZ in pure solution and in cosmetic preparation under batch condition.